Cynanchum paniculatum (Bunge) Kitag. ex H.Hara inhibits pancreatic cancer progression by inducing caspase-dependent apoptosis and suppressing TGF-β-mediated epithelial-mesenchymal transition - Cheng, Chien-Shan; Wu, Yuan; Jin, Jia-Bin; Xu, Jia-Yue; Yang, Pei-Wen; Zhu, Wen-Hua; Zheng, Lan; Chen, Jing-Xian (Frontiers in Pharmacology, 2024)
Background: Cynanchum paniculatum (Bunge) Kitag. ex H.Hara, a member of the Asclepiadaceae family, has a rich history as a traditional Chinese medicinal plant used to treat digestive disorders. However, its potential anti-cancer effects in pancreatic cancer remain largely unexplored.Aim: This study delves into the intricate anti-pancreatic cancer mechanisms of Cynanchum paniculatum (Bunge) Kitag. ex H.Hara aqueous extract (CPAE) by elucidating its role in apoptosis induction and the inhibition of invasion and migration. Methods: A comprehensive set of methodologies was employed to assess CPAE's impact, including cell viability analyses using MTT and colony formation assays, flow cytometry for cell cycle distribution and apoptosis assessment, scratch-wound and Matrigel invasion assays for migration and invasion capabilities, and immunoblotting to to measure the expression levels of key proteins involved in apoptosis and metastasis. Additionally, a murine xenograft model was established to investigate CPAE's in vivo anti-cancer potential.Results: CPAE exhibited time-and dose-dependent suppression of proliferation and colony formation in pancreatic cancer cells. Notably, CPAE induced apoptosis and G2/M phase arrest, effectively activating the caspase-dependent PARP pathway. At non-cytotoxic doses, CPAE significantly curtailed the metastatic abilities of pancreatic cells, effectively suppressing epithelialmesenchymal transition (EMT) and downregulating the TGF-β1/Smad2/3 pathway. In vivo experiments underscored CPAE's ability to inhibit tumor proliferation.Conclusion: This study illuminates the multifaceted anti-proliferative, pro-apoptotic, anti-invasive, and anti-migratory effects of CPAE, both in vitro and in vivo. CPAE emerges as a promising herbal medicine for pancreatic cancer treatment, with its potential mediated through apoptosis induction via the caspase-dependent PARP pathway and MET suppression via the TGF-β1/Smad2/3 signaling pathway at non-cytotoxic doses. These findings advocate for further exploration of CPAE's therapeutic potential in pancreatic cancer.